Impact of Macrofaunal Communities on the Coastal Filter Function in the Bay of Gdansk, Baltic Sea - Thoms, Franziska; Burmeister, Christian; Dippner, Joachim W.; Gogina, Mayya; Janas, Urszula; Kendzierska, Halina; Liskow, Iris; Voss, Maren (Frontiers in Marine Science, 2018)
Abstract During three cruises to the Bay of Gdansk, Baltic Sea, the fauna, porewater and bottom water were sampled at stations parallel to the shore and along a transect offshore. Diffusive porewater fluxes were calculated and related to the total net fluxes (TNF) of nutrients. The TNF comprise all nutrients that reach the bottom water from the sediment including diffusive nutrient efflux, discharge from macrozoobenthos and microbial activity. They were determined during in situ incubations using a benthic chamber lander, which is rarely done in coastal research. The lander restricts the physical influence of currents and waves on the sediments and only allows nutrient fluxes due to bioturbation by natural communities. Strong benthic-pelagic coupling in the shallow coastal zone suggested a crucial filter function for the bioturbated coastal sediments, which are separated from muddy deep sediments with little or no fauna at a depth of 50 m; in between is a small intermediate zone. While diffusive fluxes were highest at intermediate and offshore stations, TNF were highest at sandy coastal stations, where reservoirs of dissolved nutrients were small and sediments almost devoid of organic material. The greatest impact of macrofauna on sedimentary fluxes was found at stations whose communities were dominated by deep-burrowing polychaetes. The largest TNF were measured directly at the mouth of the Vistula River, where riverine food and nutrients supplies were highest. Macrofauna communities and sediment variables can thus serve as descriptive indicator to estimate the extent of the coastal filter. Finally, based on the total areal size of the different sediment types, annual efflux for the complete coastal zone of the Gdansk Bay was estimated to be 6.9 kt N, 19 kt Si, and 0.9 kt P. Compared to the muddy offshore area, which is twice as large, these amounts were similar for P and threefold higher for N and Si.